Tumor stroma as targets for cancer therapy - Zhang, Jing (2012)
Cancer is not only composed malignant epithelial component but also stromal components such as fibroblasts, endothelial cells, and inflammatory cells, by which an appropriate tumor microenvironment (TME) is formed to promote tumorigenesis, progression, and metastasis. As the most abundant component in the TME, cancer-associated fibroblasts (CAFs) are involved in multifaceted mechanistic details including remodeling the extracellular matrix, suppressing immune responses, and secreting growth factors and cytokines that mediate signaling pathways to extensively affect tumor cell growth and invasiveness, differentiation, angiogenesis, and chronic inflammatory milieu. Today, more and more therapeutic strategies are purposefully designed to target the TME as well as tumor cells. This review will focus on the role of CAFs in tumor development and the novel strategies to target this component to inhibit the tumor growth.